FUNCTIONS OF LAUGHTER AND CRYING IN UZBEK AND ENGLISH - Azimova Muxtasarxon Jaloldin qizi; Qurbonova Mohichehra Mahmud qizi (Journal of Creativity in Art and Design, 2024)
Laughter and crying are complex emotional expressions that play essential roles in human development, social interactions, and psychological well-being (Darwin, 1872; Provine, 2000). As fundamentally communicative acts, both laughter and crying transcend linguistic barriers, allowing individuals to express emotions and convey messages to others nonverbally (Ekman & Friesen, 1971). Laughter, often associated with joy and humor, has been shown to promote social bonding, alleviate stress, and trigger physiological responses that enhance well-being (Martin, 2002). Conversely, crying serves as a signal of vulnerability and need, eliciting empathy and support from others (Vingerhoets, 2013). However, both responses can appear in complex contexts; for example, people may laugh in uncomfortable situations or cry from joy, which illustrates the adaptive flexibility of these behaviors in coping with emotional challenges (Freud, 1905; Ruch, 1993). By examining the evolutionary, neurological, and social functions of laughter and crying, this study aims to deepen our understanding of these expressions as essential components of human emotional experience, offering insight into their role in mental health and interpersonal relationships.